EXTENSION COMMUNICATION COMPETENCE AND COUNSELING INTENSITY ON THE QUALITY OF FAMILY PLANNING EXTENSION SERVICES IN AN EFFORT TO REDUCE STUNTING IN NORTH PADANG LAWAS REGENCY - Nasution, Sofya Rahma; Lubis, Lusiana Andriani; Achmad, Nurman (International Journal of Social Service and Research, 2024)
The stunting phenomenon is a difficult task for family planning extension workers in North Padang Lawas Regency, as well as a concern for the local government to provide assistance to families at risk of stunting. The purpose of this study is to analyze the influence of communication competence of extension workers on the quality of Family Planning (KB) extension services in an effort to reduce the stunting and how much influence the communication competence and counseling intensity have on the service quality of family planning. The study is based on a cross-sectional study, and the population is couples of childbearing age who are the target group of assistance by family planning Extension Workers in an attempt to reduce stunting in the community. The results of the study showed that communication competence significantly impacted service quality by 38.6%. Communication competence and extension intensity had a significant impact on service quality 80.9%. The findings can be used by extension workers to improve service quality and ensure adequate competence in stunting prevention programs.